2022
DOI: 10.3390/children9060884
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease: Growth Evaluation and Sport Activity in a Paediatric Population

Abstract: (1) Objective: To evaluate: (i) the associations of age and disease severity with anthropometric indices and weight status, (ii) the difference in the frequency of sports activity among different levels of disease severity in paediatric patients with congenital heart disease (CHD). (2) Methods: Clinical data of Caucasian children (aged 2–18 years) diagnosed with CHD (2005–2018) were retrospectively collected from the electronic register of outpatient visits. Of the 475 children with CHD, 368 children and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Despite the fact that mild and moderate congenital heart disease has a similar prevalence of obesity, the probability is lower in patients with severe lesions. [15] That trend has been observed in various ethnic groups.…”
Section: Discussionmentioning
confidence: 78%
“…Despite the fact that mild and moderate congenital heart disease has a similar prevalence of obesity, the probability is lower in patients with severe lesions. [15] That trend has been observed in various ethnic groups.…”
Section: Discussionmentioning
confidence: 78%
“…The mean BMI in preschoolers with CHD was insignificantly lower than that of the healthy controls. Previous studies reported that the risk of obesity in children with CHD increased over time, especially in patients with mild CHD [ 27 , 28 ]. Adipose composition varies among countries and age groups.…”
Section: Discussionmentioning
confidence: 99%